A meta-study of qualitative research on mental toughness development. Issue 1 (1st January 2016) - Anthony, David R.; Gucciardi, Daniel F.; Gordon, Sandy
ABSTRACT: Mental toughness (MT) is considered a necessary ingredient for high-level performance. Unsurprisingly, scholarly interest in the development of mental toughness has increased over the past decade, with much of this work informed by qualitative designs. No study to date has systematically reviewed and integrated this body of qualitative research on MT development. The primary purpose of this study was to create an integrated theoretical framework that incorporates extant MT development research in sport and performance settings. Three subsequent aims were to (a) systematically review and evaluate the qualitative literature regarding key developmental factors and processes for MT; (b) synthesise knowledge of key developmental factors and processes for MT; and (c) generate an integrated framework that can inform future research and advancement in theory with regard to MT development. Following a systematic search of online journals, search engines, and databases, 10 papers met the criteria for inclusion and were retained. These studies served as the primary data for meta-data, meta-method, and meta-theory analyses, which were integrated using a meta-synthesis approach. Four key themes were identified from the existing qualitative evidence: personal characteristics, interactions with environment, progressive development, and breadth of experience. These unique themes were integrated with existing theory to propose a bioecological model of MT development that encompasses interdependent interactions among the person, proximal processes, context, and time. We describe how this model can be used as a heuristic for research and practice, and underscore the importance of methodological diversity for future work on the development of MT.